NEW NORMAL PARIWISATA BALI DI MASA PANDEMI PADA DAERAH TUJUAN WISATA TANAH LOT, KABUPATEN TABANAN - Astrid Krisdayanthi (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2020)
Covid-19 has profoundly affected the economy today. Not only has income decreased, but the number of unemployed has also continued to increase. The tourism sector, which drives the economy in Bali, was also affected. Many tourism workers have to be laid off and also many have lost their livelihoods as a result of the Covid-19 pandemic. The purpose of this article is to find out the state of Tanah Lot since the implementation of the new life adaptation by the government. The method used is a qualitative descriptive method to understand the new normal phenomenon of tourism. The data from this research is based on literature study in the form of literature in the form of books, journals, articles, interviews with tourism actors and also observations in the field. The new normal that has been in effect today is like a breath of fresh air for the community and also for the tourism business. This is because with the enactment of the new normal while adhering to the applicable Health protocols, people can start working again and tourism can start to reopen. The Tanah Lot tourist destination, which has been closed as part of preventing the spread of Covid-19, has now reopened but still adheres to the Health protocol. The operational manager of the Tanah Lot tourist destination, Mr. Toya Adnyana, said that the Tanah Lot tourist attraction was ready with standard operating procedures related to new normal tourism. His party has prepared according to the applicable Health protocol standards to enter this new normal phase, such as; masks, face shields for ticketing and checking tickets, portable sinks in several areas, appeals regarding health protocols and hand sanitizers. With the opening of the Tanah Lot tourist destination to receive tourist visits, this has a positive impact on tourism actors around it. Even though the impact has not been felt yet because the number is still small, it is enough to help those who have lost their income for the past 4 months due to the closure of the Tanah Lot tourist destination.